2018
DOI: 10.1016/j.envpol.2018.02.067
|View full text |Cite
|
Sign up to set email alerts
|

In vitro profiling of toxic effects of prominent environmental lower-chlorinated PCB congeners linked with endocrine disruption and tumor promotion

Abstract: The mechanisms contributing to toxic effects of airborne lower-chlorinated PCB congeners (LC-PCBs) remain poorly characterized. We evaluated in vitro toxicities of environmental LC-PCBs found in both indoor and outdoor air (PCB 4, 8, 11, 18, 28 and 31), and selected hydroxylated metabolites of PCB 8, 11 and 18, using reporter gene assays, as well as other functional cellular bioassays. We focused on processes linked with endocrine disruption, tumor promotion and/or regulation of transcription factors controlli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…In addition to acting as metabolism-disrupting chemicals, PCBs are also established endocrine-disrupting chemicals through their interactions with endocrine receptors (Luthe et al, 2008). Most low molecular weight PCBs that are not heavily chlorinated are known to activate estrogen receptors (ERα and ERβ) and antagonize AR (Pencikova et al, 2018). Higher molecular PCB congeners that are more heavily chlorinated are considered antiestrogenic and this is relevant to sex-specific effects (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acting as metabolism-disrupting chemicals, PCBs are also established endocrine-disrupting chemicals through their interactions with endocrine receptors (Luthe et al, 2008). Most low molecular weight PCBs that are not heavily chlorinated are known to activate estrogen receptors (ERα and ERβ) and antagonize AR (Pencikova et al, 2018). Higher molecular PCB congeners that are more heavily chlorinated are considered antiestrogenic and this is relevant to sex-specific effects (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the discrepant findings of the association between hydroxylated PCB exposure and cognitive performance are not known but could be linked to the diverse effects of PCB metabolites on dendritic architecture (see Section 3) and/or endocrine disruption. Hydroxylated PCBs have a differential ability to agonize or antagonize steroid hormone pathways [95], and in vitro evidence indicates that estrogenic effects of hydroxylated PCBs can be greater than that of their parent compound [96]. Maternal serum levels of hydroxylated PCBs have also been associated with free thyroxin levels in neonates [97], suggesting disruption of thyroid hormone signaling may influence the effects of hydroxylated PCB on cognition.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 99%
“…For example, the estrogenic chemical bisphenol A has been linked to abnormal lower urinary tract function [236,239]. Several PCBs have been identified to have estrogenic activity [96], but whether they alter urinary function is unknown. Of particular relevance to the question of whether developmental PCB exposures alter bladder function, developmental exposure to TCDD has been documented to disrupt lower urinary tract function [237,238].…”
Section: A Role For Pcbs In Asd Comorbidities?mentioning
confidence: 99%
“…Non‐ ortho ‐substituted PCBs 80 and 126 had no effect on GJIC. Lower‐chlorinated PCB (dichloro‐ and trichloro‐) congeners also express potencies in disruption of GJIC at micromolar concentrations (Pěnčíková et al, 2018). Hemming, Warngard and Ahlborg (1991) suggested that GJIC inhibition increases with the number of chlorinated ortho positions.…”
Section: Polychlorinated Biphenyl Congener Specific Effects On Cell Mmentioning
confidence: 99%